2017
DOI: 10.1177/0146167217713191
|View full text |Cite
|
Sign up to set email alerts
|

Individual Perceptions of Self-Actualization: What Functional Motives Are Linked to Fulfilling One’s Full Potential?

Abstract: Maslow's self-actualization remains a popular notion in academic research as well as popular culture. The notion that life's highest calling is fulfilling one's own unique potential has been widely appealing. But what do people believe they are doing when they pursue the realization of their full, unique potentials? Here, we examine lay perceptions of self-actualization. Self-actualizing, like any drive, is unlikely to operate without regard to biological and social costs and benefits. We examine which functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 30 publications
3
77
0
2
Order By: Relevance
“…However, at the same time, they add to the weight of a self-realization goal in today's relationship. These findings are in line with the findings of Krems, Kenrick, and Neel [52] which suggested that -participants anticipate their self-actualizing to involve not only finding a desirable mate, but also retaining him or her‖ (p. 8), and that -even these lofty outcomes (i.e., pursuing self-actualization) may be linked to biologically and socially relevant payoffs‖ (p.13).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, at the same time, they add to the weight of a self-realization goal in today's relationship. These findings are in line with the findings of Krems, Kenrick, and Neel [52] which suggested that -participants anticipate their self-actualizing to involve not only finding a desirable mate, but also retaining him or her‖ (p. 8), and that -even these lofty outcomes (i.e., pursuing self-actualization) may be linked to biologically and socially relevant payoffs‖ (p.13).…”
Section: Discussionsupporting
confidence: 88%
“…This present study suggests that self-actualization is not a new element that becomes a sufficient condition complementing sexual activity (Factor 2) in order to get relationship satisfaction. Already since 1978, Paxton and Turner [53, p.66] explained that -certain types of sexual attitudes and behaviors may be characteristic of self-actualizing females.‖ Thus, in line with the predictions and the results of previous studies [52], self-actualization does not stand independent and become the ultimate relationship goal especially in the romantic one. Rather, on the contrary, through regression analysis (with sexual satisfaction as the dependent variable), selfactualization is found to be devoted to sexual activity [53], which has been robustly proved pivotal as a contributor to relationship satisfaction [54,55].…”
Section: Discussionmentioning
confidence: 90%
“…"self-actualization, which is about fully realizing your own potential," and 3) "hedonic wellbeing, which is about maximizing the amount of pleasure in your life (and minimizing the amount of pain)" (Krems et al, 2017). Those participants (N = 565, Mage = 37.97, SD = 13.00)…”
Section: Family Matters 17mentioning
confidence: 99%
“…18 Figure 7. Results from Krems, Kenrick, & Neel (2017) Study 2, displaying which motives participants said they would be focused on right now if they were pursuing one of three different types of well-being; (A) Eudaimonic well-being (i.e., finding meaning and purpose in life), (B)…”
Section: Family Mattersmentioning
confidence: 99%
“…Finally, although these evolved motivational systems are characterized as “fundamental” because of their evolutionary origins and not because of their consequences for subjectively valued psychological states, they may nonetheless guide individuals' pursuit of happiness and personal fulfillment. This is because reward mechanisms (e.g., neurochemical regulation of affective states) are integral to the suites of psychological adaptations that characterize these fundamental motives—with the consequence that many things that make people feel happy or fulfilled correspond to the successful pursuit of fundamental motives (Buss, ; Krems, Kenrick, & Neel, in press; Nesse & Ellsworth, ). That said, it is important to remember that an evolutionary perspective on human motivation is not defined by questions about what makes us healthy or happy; it focuses more fundamentally on what makes us human.…”
Section: Additional Implicationsmentioning
confidence: 99%